Validation of the Bedtime Procrastination Scale Among Korean High School Students During the COVID-19 Pandemic - Jaeeun Song; Oli Ahmed; Taeyeop Lee (Sleep Medicine Research)
Background and Objective This study aimed to investigate the reliability and validity of the Bedtime Procrastination Scale (BPS) among Korean high school students during the COVID-19 pandemic. Methods We conducted an online survey among a total of 300 high school students from October 18–24, 2021. We performed confirmatory factor analysis (CFA) on the two-factor model of the BPS. Psychometric properties were explored using the Graded Response Model and Rasch model. The reliability of internal consistency was assessed using Cronbach’s alpha. Convergent validity was examined regarding depression using the Patient Health Questionnaire-9 items and viral anxiety using the Stress and Anxiety to Viral Epidemics-6 items. Results The CFA results indicated a strong model fit for the BPS (χ2/df=0.597, CFI=1.000, TLI=1.012, RMSEA=0.000, and SRMR=0.040). Additionally, the BPS demonstrated strong reliability (Cronbach’s alpha=0.824). Bedtime procrastination was significantly correlated with depression (r=0.31, p<0.001) but not with viral anxiety. Conclusions The BPS is reliable and valid in assessing high school students, and bedtime procrastination is significantly associated with depression.